Analisis Strategi Pengembangan Usaha Supermarket XYZ dengan Pendekatan Model Bisnis Kanvas - Soselisa, Jack Absalom; Raharja, Sapta; Suharjo, Budi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2017)
The purpose of the research is to identify and analyze the business model in Supermarket XYZ,  then give recommendation of priority strategy as perfection of Supermarket XYZ business model to more systematic, specific, unique and relevant to current business condition.   This research uses descriptive analysis method. The analytical tool used is business model canvass (BMC), the external factor evaluation matrix (EFE), internal factor evaluation matrix (IFE), external internal matrix (IE), and the combination between  strength, weakness, opportunity, threat (SWOT), and analytical hierarchy process (AHP )  called  AWOT.  The  result was obtained based on the result of AWOT analysis,  the priority strategy of the channel element with the highest score is SO strategy, to develop a food court to provide a customer shopping experience. Priority strategy of the customer relationship element is ST strategy, cooperation with the third parties for the development of joint promotion programs.  Finally, priority strategy of the key activities element is WO strategy,  training and development program.  The Selected BMC element and the specified strategy can be the basis for the development of the Supermarket XYZ business model in the future.